Flexural and Impact Strength of Poly Methyl Methacrylate Incorporated with Hydroxyapatite Nanoparticles. - Saif Mohanad Al-Obaidy; Ammar Khalid Al-Noori (University of Mosul, College of Dentistry, 2024)
Aims: To investigate the effects of the incorporation of hydroxyapatite nanoparticles (HA NPs) with size (20 nm) at two concentrations (0.5% and 1%) on the flexural strength and impact strength of heat-cured acrylic resin. Materials and methods: The total number of specimens was sixty which were divided into two groups, thirty specimens for each test (flexural strength test and impact strength test), ten specimens for each subgroup (control, 0.5 % HA NPs and 1 % HA NPs), the flexural strength was performed using the universal testing machine, and impact strength using Charpy impact tester. The statistical analysis was done by using the SPSS program including descriptive statistics, ANOVA, and Duncan's test at p ≤ 0.05. Results: The results demonstrated that there was a significant increase in the flexural and impact strength for the PMMA-HA nanocomposite at HA nanoparticles (0.5%) and (1%) when compared to control. Conclusion: the use of hydroxyapatite nanoparticles as dental fillers at 0.5% and 1% by weight enhanced the flexural strength and impact strength of PMMA denture base material.